Epidemiology of obesity and overweight in sub-Saharan Africa: a protocol for a systematic review and meta-analysis. Issue 11 (25th November 2017) - Biadgilign, Sibhatu; Mgutshini, Tennyson; Haile, Demewoz; Gebremichael, Bereket; Moges, Yonatan; Tilahun, Kelemu
Abstract : Introduction: Globally, overweight and obesity were estimated to cause 3.4 million deaths, 3.9% of years of life lost and 3.8% of disability-adjusted life years in 2010. Despite the fact that obesity and overweight is a problem of high-income countries, low- and middle-income countries (LMICs), in particular urban settings of sub-Saharan African countries, face the challenge of an increasing trend. The aim of this systematic review and meta-analysis will be to determine the prevalence of obesity and overweight individuals in sub-Saharan Africa and to help guide policy planners in the decision-making process for the increase in non-communicable diseases in Africa. Methods and analyses: A comprehensive systematic review and meta-analysis of published studies on the prevalence of obesity and overweight in sub-Saharan Africa will be conducted. A computerised internet search using Medline/PubMed, Google Scholar and EMBASE databases and reference lists of previous prevalence studies and detailed search strategy and cross-checking of reference lists of published peer-reviewed articles will be conducted to identify all epidemiological and/or clinical studies published in English and French. We will use the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) statement for reporting. The overall effect (pooled estimated effect size) of the prevalence of obesity and overweight will be analysed using the Der Simonian–Laird random effects meta-analysis (random effects model) and the obesity proportion (with 95% CI) will be measured. Ethics and dissemination: The underlying work is based on systematic reviews of published data and thus doed not require ethical review approval. The findings of the systematic review will be disseminated in different conferences and seminars and will be published in a reputable and refereed international peer-reviewed journal. PROSPERO registration number: CRD42017064942.